Patterns of alternative tobacco product experimentation among ever smoker adolescents - Pénzes, Melinda; Foley, Kristie L; Balázs, Péter; Urbán, Róbert (Central European journal of public health, 2019)
OBJECTIVES: Alternative tobacco product (ATP) use is popular among adolescents in Western countries, however, little is known about factors influencing ATP experimentation in Europe. The aim of this study was to explore factors associated with ATP experimentation, and to identify patterns of ATP experimentation among Hungarian adolescents who had ever tried manufactured cigarette smoking. METHODS: Logistic regression analyses were applied to estimate the relationship between individual cigarette smoking experiences, social smoking influences, demographics, and ATP experimentation (roll-your-own (RYO) cigarettes, cigars/cigarillos, waterpipe, traditional pipe and flavoured cigarettes) in a cross-sectional sample of 8th and 11th grade students (N = 1,067, 56.0% of girls) who had ever tried manufactured cigarette smoking in six metropolitan cities of Hungary. Latent class analysis (LCA) was performed to identify patterns of different ATP use. RESULTS: Almost 90% of the sample had ever tried ATPs and significantly more commonly older (91.8%) versus younger (79.8%) students. Waterpipe was the most popular product to try followed by flavoured cigarettes, cigars/cigarillos, RYO cigarettes, and pipe. Boys were more likely to report ATP experimentation compared to girls. Younger age of cigarette smoking experimentation, greater frequency of past month cigarette smoking and history of ever daily smoking for 30 days showed strong association with ATP experimentation. Students with one or more smoking friends were more vulnerable to experiment with ATPs. Weekly allowance, school academic achievement and household smoking exposure showed no effect on the experimentation. LCA identified four subgroups of ATP experimenters comprising intense polytobacco experimenters (38.4%), mainly waterpipe experimenters (34.2%), moderate polytobacco experimenters (14.9%), and less interested experimenters (12.5%). CONCLUSION: Tobacco prevention programmes targeting adolescents should emphasize the risks of using ATPs in addition to manufactured cigarettes. Accessibility of ATPs should be better regulated and restrictions should be strongly enforced in order to prevent potential harmful consequences of adolescent polytobacco use.
Keywords: Tobacco Products; latent class analysis; Humans; Smokers; chování mladistvých; kuřáci; smoking; Female; lidé; adolescent; Hungary; Maďarsko; alternative tobacco products; tabákové výrobky; ženské pohlaví; Male; Adolescent Behavior; tobacco; Adolescent; Cross-Sectional Studies; Smoking; mužské pohlaví; kouření; průřezové studie; mladiství